The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0735633115597490
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Peer Review and Teachers' Corrective Feedback on EFL Students' Online Writing Performance

Abstract: The purpose of this study was to compare the effects of the combination of teacher-led feedback and peer review (TF + PR) and a single TF method on the writing performance of English as a foreign language (EFL) university students within a collaborative online learning system. The students' perceptions of the writing course were also examined. An experimental PR + TF group and a comparison TF group, with a total of 107 undergraduate students majoring in nursing, participated in this study during the fall semes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 31 publications
(46 reference statements)
9
49
0
1
Order By: Relevance
“…The collaborative learning activity involved the peer feedback rubric and checklist, PSETs' learning time-line and planning through the communication format, instruments, meeting schedule and evaluation. Tai, Lin, and Yang (2015) emphasized that the peer feedback led to enhance the effectiveness of the course delivery and to apply stronger collaborations into PSETs' learning. Genre-based writing classes proved to be more meaningful and more effective, since the PSETs were well-facilitated by the certain feedback devices that accommodated the objectives and learning motivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collaborative learning activity involved the peer feedback rubric and checklist, PSETs' learning time-line and planning through the communication format, instruments, meeting schedule and evaluation. Tai, Lin, and Yang (2015) emphasized that the peer feedback led to enhance the effectiveness of the course delivery and to apply stronger collaborations into PSETs' learning. Genre-based writing classes proved to be more meaningful and more effective, since the PSETs were well-facilitated by the certain feedback devices that accommodated the objectives and learning motivation.…”
Section: Resultsmentioning
confidence: 99%
“…Genre is a term for grouping texts together, representing how writers typically use language to respond to recurring situations (Hyland, 2008) within generating and organizing ideas by using an appropriate choice of vocabulary, sentence, and paragraph organization, as well as turning such ideas into a readable text (Richards & Renandya, 2002;Widodo, 2006). According to Tai, Lin and Yang (2015), writing assessment consists of five equally weighted criteria, such as content-the logical development of ideas; organizationintroduction, body, and conclusion; grammar; mechanics-punctuation, spelling, and vocabulary use; and style-writing style and quality of expression. This means responding to the specific instructional contexts, L1 or L2 and experience, writing purposes and providing extensive encouragement in the form of meaningful contexts, peer involvement, prior texts, useful feedback and guidance in the writing process (Hyland, 2003) to coordinate and integrate their linguistic usage (Kern, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some evidence that students benefit more from giving peer response comments than receiving them (Lundstrom & Baker, 2009), it has remained a priority to measure the impact of peer response on subsequent drafts (Chaudron, L2 Journal Vol. 11 Issue 1 (2019) 39 1984; Connor & Asenavage, 1994;Flynn, 1982;McGroarty & Zhu, 1997;Min, 2006;Ruegg, 2015;Tai, Lin, & Yang, 2015;Tsui & Ng, 2000;Villamil & Guerrero, 1998). Some studies have found that students who receive comments from trained peer responders incorporate more of these changes into subsequent drafts (Min, 2006).…”
Section: Research On Peer Responsementioning
confidence: 99%
“…Although peer review has been found to be effective in improving students' writing scores, comparisons between peer feedback and teacher feedback have resulted in mixed findings as to which type of feedback is more effective in improving writing quality. Tai, Lin, and Yang (2015) explored whether peer review with teacher feedback or teacher feedback were more effective in the context of the college ESL classroom. Students who received peer review with teacher feedback performed better than the students who did not in their study.…”
Section: Achenmentioning
confidence: 99%
“…Interestingly, peers judged to be less competent did not provide feedback that was perceived to be less adequate for the writer. In a study of perceptions of peer reviewers, Tai et al (2015) found students enjoy peer review and believe they can learn from their peers. However, students also were concerned about the quality of peer reviewers' opinions and felt they provided mostly superficial feedback.…”
Section: Achenmentioning
confidence: 99%